AT1 RECEPTOR BLOCKADE AND AT2 RECEPTOR STIMULATION EFFECT ON THE RAS PEPTIDE LEVELS IN THE PREVENTION AND TREATMENT OF EXPERIMENTAL AUTOIMMUNE MYOCARDITIS (EAM) IN MALE LEW. (June 2018) - Paulis, L.; Rajkovicova, R.; Domenig, O.; Trubacova, S.; Kashina, E.; Kintcher, U.; Unger, T.; Steckelings, M.; Poglitsch, M.; Schmerler, P.
Abstract : Objective: EAM is characterized by transient myocarditis (peak at day 21), progressive fibrosis, hypertrophy (evolving from concentric to dilation type), dysfunction and subsequent heart failure (day 35). Design and method: We have investigated the effects of the AT2 receptor agonist, compound 21 (C21) and olmesartan on RAS peptide and receptor levels when given in prevention (day 0–21 post EAM-induction) or reversion (day 21–35 post EAM-induction) of EAM. C21 prevented myocardial infiltration and reversed hypertrophy without affecting blood pressure, while olmesartan prevented myocardial infiltration, fibrosis and dysfunction and reversed hypertrophy, dilation and dysfunction. Only the combination of C21 and olmesartan significantly reversed already established myocardial fibrosis. Results: Our EAM model demonstrated high renin, Ang I and II levels, with transient (day 21) decline of angiotensinogen (AGT) levels. The tissue Ang II levels were exceptionally increased in EAM, putatively due to higher ACE activity or increased AT1 receptor expression. Olmesartan augmented AGT depletion (at day 21 and causing depletion at day 35), with consequent absence of reactive plasma Ang II, observed in other models. Moreover, olmesartan strongly reduced myocardial Ang II levels. C21 prevented AGT decline, with consequent increase in Ang II concentration despite increased aminopeptidase-dependent degradation. The LV AT2 receptor expression increased progressively with the evolvement of the EAM-induced heart failure. Conclusions: In conclusion, C21 prevented AGT exhaustion in EAM rats. The consequently higher Ang II levels might have offset the beneficial effects of the AT2 receptor stimulation in EAM. Particularities of the RAS modulation affect the therapeutic outcome in distinct cardiovascular pathologies that appear clinically similar. (VEGA 1/0127/17)